PENGARUH KEGIATAN MUHADHARAH DAN MUDZAKARAH TERHADAP HASIL BELAJAR AQIDAH AKHLAK DI MTs NURUL ATHFAL CIKULUR - Fikri Dzikrillah (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2019)
The objectives of this study are: 1). To find out the level of student participation in participating in Muhammadiyah activities at MTs Nurul Athfal Cikulur. 2). To find out the level of student participation in participating in mudzakarah activities at MTs Nurul Athfal Cikulur. 3). Knowing the Effect of Muhadharah and Mudzakarah activities on the learning outcomes of aqidah morality of students at MTs Nurul Athfal Cikulur. This research method uses quantitative analysis methods to see the effect of variables with multiple linear regression testing using the T-test (Partial), F (Simultaneous) Test, Correlation Coefficient, and the coefficient of determination R2 (R Square), and consider the classical assumption test namely Normality. The results showed that a partial analysis (t test) of Muhadhrah activities and Mudzakarah activities, it was found that both of these variables had an influence on the learning outcomes of Aqidah Akhlah in MTs Nurul Athfal Cikulur, this is indicated by the value of t arithmetic> t table respectively of (2.184 )> (1,671) and (3,540)> (1,671). Simultaneously Muhadhrah activities and Mudzakarah activities, it was found that both of these variables had an influence on the learning outcomes of Aqidah Akhlah in MTs Nurul Athfal Cikulur as indicated by the calculated F value> F table = 13,671)> (3.16), the magnitude of the influence of Muhadhrah activities and Mudzakarah activities, found both of these variables have an influence on the learning outcomes of Aqidah Akhlah in MTs Nurul Athfal Cikulur Serang assistant at 56.9% indicated from the R Square value of 0.569.